Snake Bites in Sulaimani – Iraq - Hawramy, Tahir A. Husen. (Sulaimani Journal for Pure and Applied Sciences, 2004)
A study of the characteristics of snake bites in Sulaimani Governorate was undertaken during April 1997 to October 1997. It is found that all signs of envenomation were seen and the most affected age groups by snake bites were between 11-20 years. Snaketrite were more frequent among rnale than fr:mal l'amrers. More cornmon iri iemperate ereas. Most features were necrotising and vascultoxic than myotoxic .No significant differences found between the seven months which were involved in the study, fleither between the four affected sites ofthe body according to numhers ofthe cases.
Keywords: Snake bites in Sulaimani; future planning for producing spiciffic ant venom